Pengaruh Model Pembelajaran Small Group Discussion (SGD) pada Pembelajaran Tematik untuk Meningkatkan Keaktifan Berbicara Siswa Kelas V MIN 4 Bone - Reka, Reka; Ramadan, Syahru (Madrasah Ibtidaiyah Research Journal, 2023)
This research aims to see the effect of the Small Group Discussion (SGD) model on thematic learning to increase students' active speaking at MIN 4 Bone. This research studied the influence of the application of the Small Group Discussion (SGD) learning model on students' active speaking by teachers at MIN 4 Bone. This type of research used is quantitative research with survei methods. The location of this research is MIN 4 Bone. There are also data collection techniques used, namely through observation, questionnaires, and documentation. The subjects of this research were 18 students in class V MIN 4 Bone. The results of this research indicate that the Small Group Discussion (SGD) model has an influence on increasing students' active speaking. This can be seen in the correlation test value between the SGD learning model and active speaking of 0.643, which means it has a strong level of relationship. The relationship is in the category interval between 0.60-0.799. That is, the SGD model has a positive effect on students' active speaking with a strong relationship category. Then, the significance level is 0.000 so the number is smaller than 0.05. It means that the influence between the two variables is significant. Thus, the SGD learning model has an effect on increasing the activeness of speaking class V MIN 4 Bone students.